PSIKOEDUKASI BERSIAGA UNTUK MENUMBUHKAN KESIAPAN MENGHADAPI KEHIDUPAN PERNIKAHAN - Annisa, Nida Muthi; Hermawan, Cyndi Fiolandha; Amos, Amos; Nahrudin, Muhammad Novan Rhamdani (Jurnal Sosial & Abdimas, 2025)
A marriage bond needs to be built and formed from the readiness of each individual to build a family. In Indonesia, there is a phenomenon of postponement of marriage. Many young people aged 16-30 years have decided to postpone marriage which is supported by a decrease in the marriage rate in the last 10 years. In addition to the decrease in the marriage rate, it is also marked by an increase in the divorce rate in the 2021-2022 period. Based on this phenomenon, indicates a lack of community readiness in building a marriage bond. Marriage readiness is important to have to form a family that is good physically, socially emotionally, sexually, morally and committed. Psychoeducation related to marriage preparation is one way to form marriage readiness. The purpose of implementing this PKM activity is to change negative perceptions about marriage and provide an understanding of marriage preparation for unmarried young adults. The results of the pretest and posttest given obtained a higher mean posttest value compared to the pretest. Based on the evaluation of the activities given to the participants, psychoeducation was able to provide a better perception of marriage and increase early adult understanding of preparation for building a marriage. This indicates that psychoeducation can provide new understanding information for early adult individuals' marriage readiness. Suatu ikatan pernikahan perlu dibangun dan dibentuk dari adanya kesiapan masing-masing individu dalam membangun sebuah keluarga. Di Indonesia terdapat fenomena penundaan pernikahan. Pemuda di usia 16-30 tahun banyak yang memutuskan untuk menunda pernikahan yang didukung dengan penurunan angka pernikahan pada 10 tahun terakhir. Selain penurunan angka pernikahan juga ditandai dengan peningkatan angka perceraian di kurung waktu tahun 2021-2022. Berdasarkan fenomena tersebut mengindikasikan kurangnya kesiapan masyarakat dalam membangun ikatan pernikahan. Marriage readiness penting dimiliki agar dapat terbentuk keluarga yang baik secara fisik, sosial emosional, seksual, moral dan komitmen. Psikoedukasi yang berkaitan dengan persiapan pernikahan merupakan salah satu cara membentuk marriage readiness. Tujuan dari pelaksanaan kegiatan PkM ini adalah untuk mengubah persepsi negatif tentang pernikahans serta memberikan pemahaman tentang persiapan pernikahan pada dewasa awal yang belum menikah. Berdasarkan evaluasi kegiatan yang diberikan pada peserta, psikoedukasi mampu untuk memberikan persepsi yang lebih baik tentang pernikahan serta menambah pemahaman dewasa awal tentang persiapan membangun sebuah pernikahan.